The pediatric nasal microbiome and its role in chronic ENT disorders: a narrative review - Sîrbu, Adriana Elena; Gradisteanu Pircalabioru, Gratiela; Deaconu, Diana Maria; Andronic, Octavian; Gheorghe, Dan Cristian (Frontiers in Immunology, 2026)
The human microbiome is increasingly recognized as a key factor in immune development and disease susceptibility, especially in early life. Nasal microbiome has emerged as a critical element in upper airway health, yet its role in pediatric otorhinolaryngological conditions remains underexplored. This narrative review synthesizes current evidence on the microbial nasopharyngeal patterns in healthy children compared with children suffering from chronic ENT conditions such as otitis media, allergic rhinitis, chronic rhinosinusitis, adenoid and tonsillar hypertrophy associated with obstructive sleep apnea. A structured search of Web of Science, PubMed, Google Scholar and CrossRef databases was conducted for peer-reviewed articles published in the past ten years. Nasal microbiota of healthy children was proved to be dominated by commensal protective taxa such as Dolosigranulum and Corynebacterium which contribute to mucosal immune stability. In contrast, patients with chronic ENT pathologies exhibited reduced diversity and increased prevalence of potential pathogens microbial species such as Haemophilus, Streptococcus and Staphylococcus. Several extrinsic factors appear to play an important role in modulating the nasal microbiota such as environmental exposure, delivery mode, feeding practices and antibiotic treatment. Growing evidence supports the predictive and modulatory potential of the nasal microbiome, however methodological variability, limited pediatric-specific studies and unclear causal relationships remain challenging components. This review highlights key microbial patterns, outlines the limitations of current research and suggests future directions for clinical integration of nasal microbiome analysis in pediatric ENT standard of care as it may hold promising utilisation of biomarkers for disease risk stratification and targeted therapeutic or preventative interventions in early life.